2019
DOI: 10.1186/s12931-019-1132-9
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial thermoplasty increases airway volume measured by functional respiratory imaging

Abstract: Background: The purpose of this study was to use CT scanning with computational fluid dynamics to evaluate the mechanisms by which Bronchial Thermoplasty (BT) improves asthmatic symptoms. Methods: The study was conducted in a university teaching hospital, experienced in performing BT. Imaging studies were performed before, and after, BT of the left lung, and prior to treatment of the right lung, which therefore acted as a control. On each occasion, two high-resolution CT scans were performed, one at full inspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
5
21
0
Order By: Relevance
“…Plethysmography has demonstrated a reduction in the degree of gas trapping (measured by residual volume) after BT, but the magnitude of this change was modest [11]. The first compelling evidence for an improvement in lung physiology after BT was presented in our recent paper, which used a CT-based segmentation methodology to demonstrate that the volume of air in the airways increased following BT treatment [12].…”
Section: Background and Aimmentioning
confidence: 99%
“…Plethysmography has demonstrated a reduction in the degree of gas trapping (measured by residual volume) after BT, but the magnitude of this change was modest [11]. The first compelling evidence for an improvement in lung physiology after BT was presented in our recent paper, which used a CT-based segmentation methodology to demonstrate that the volume of air in the airways increased following BT treatment [12].…”
Section: Background and Aimmentioning
confidence: 99%
“…This allowed patients to be re-evaluated mid treatment with our CT scanning protocol, with the left lung completely treated but the right lung being untreated and serving as a control. This treatment protocol is reported elsewhere, but is included here in order to assist with the interpretation of the changes to the various lung function parameters [10,18]. In this present study, patients were evaluated by spirometry, plethysmography and MBNW at baseline (in the 4 weeks prior to BT) and then again, 6 weeks and 6 months after the completion of all BT treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, improvements in spirometry are either non-existent or modest [4][5][6][7][8]. Mathematical modelling of the physiological behaviour of the asthmatic lung, suggests that bronchial thermoplasty should result in dilatation of the treated airways and, indeed that has been demonstrated in recent computerized tomography (CT) studies [9][10][11]. This modelling also suggests that the airway dilatation should improve the downstream distribution of ventilation to small airways and recent studies of ventilation homogeneity in the lung using hyperpolarized gas magnetic resonance imaging (MRI) would lend support to this proposal [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ishii et al have reported chest HRCT at inspiratory and expiratory levels before and after BT treatment, and reported that the expiratory lung volume decreases after BT treatment (Figure 9) (14). Langton et al also reported increase of the luminal airway volume and decrease of residual volume after BT (15,16). It can be said that measurement of expiratory lung volume can be a tool for estimating the usefulness of BT treatment.…”
Section: (98)mentioning
confidence: 99%